TagHunt: Uma plataforma Combinando a Internet das Coisas com Scavenger Hunt Games - Gama, Kiev; Wanderley, Rafael; Maranhão, Daniel; Garcia, Vinicius (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP); 2015: Anais do VII Simpósio Brasileiro de Computação Ubíqua e Pervasiva, 2015)
The “Internet of Things” (IoT) brings the notion of heterogeneous objects using ubiquitous technologies to interact among them and with the physical environment through technologies such as Bluetooth, ZigBee, GPRS, NFC, QR code, among others. Based on the possibility of linking ordinary objects from the physical world to the Internet, this paper proposes and details a platform called TagHunt, for creating and playing scavenger hunt games. This platform leverages on smartphones’ capability to interact with ordinary objects using IoT-based technologies such as NFC and QR Code, stimulating the player to interact with physical environments looking for “clues” in the game.